Problems Encountered by Valenzuela Bureau of Jail Management and Penology Personnel; A Study: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In many parts of the world, jail officers play a crucial role in every jail and prison. They are theones who are in charge of maintaining peace and order among the persons deprived of liberty.Undeniably, the Philippines is experiencing a rapid increase in persons deprived of liberty(PDL) in all jails, but the number of jail officers is minimal. This research aims to determine theproblems encountered by the Valenzuela Bureau of Jail Management and Penologypersonnel in terms of the management of the person deprived of liberty, physical well-being,and maintaining peace and order. Their job is very challenging and dangerous, and possiblerisks may come unpredictably, and man-made crises are seen. Because of this, we must giveimportance to our jail officers and look after them also.The research findings show that the problems encountered by the Valenzuela Bureau of JailManagement and Penology personnel are evaluated as "sometimes" in terms of handling theperson deprived of liberty in a state of obesity, contagious diseases of the person deprived ofliberty affect the management of personnel, and a hostile person deprived of liberty will makeothers agitated and disruptive in maintaining peace and order inside the jail, and there is anintervention plan can be proposed for the solution of the problems encountered by theValenzuela Bureau of Jail Management and Penology personnel.The finding shows that the institution of the Bureau of Jail Management and Penology shouldevaluate this study and look up the intervention plan to formally address the problemsencountered by their personnel. Also, the administration should give value to our jailpersonnel and persons deprived of liberty. The researchers recommend future researcherswho desire to further expand this study to be able to contribute to the improvement of thistopic. Continuation of this research can greatly contribute to many jails due to the fact that astime passes by, problems they have encountered in jails might change.
Keywords: Criminology